FINANCIAL DERIVATIVES A FUTURE OF INDIAN FINANCIAL MARKET - Dr. Ritu Kothiwal, Mr. Ankur Goel (International Journal of Research Science and Management, 2014)
Among all the innovations that have flooded the international financial markets, financial derivatives occupy the driver's seat. These specialized instruments facilitate the shuffling and redistribution of the risks that an investor faces. Thus aids in the process of diversifying ones portfolio. The volatility in the equity markets over the past years has resulted in greater use of equity derivatives. The volume of the exchange traded equity futures and options in most of the mature markets have seen a significant growth. It goes beyond that the local derivative in the emerging markets has witnessed widespread use of the derivative instrument for a variety of reasons. This continuous growth and development by the emerging market participants has resulted in capital inflows as well as helped the investors in risk protection through hedging.